Highly sensitive detection of hydrogen peroxide at a carbon nanotube fiber microelectrode coated with palladium nanoparticles - Liu, Yang (2016)
We report on a carbon nanotube (CNT) fiber microelectrode coated with palladium nanoparticles (PdNPs) and enabling electrochemical sensing of hydrogen peroxide (H2O2). The synergistic effects of the CNT fibers (good mechanical strength and large surface area) and of the PdNPs (high electrocatalytic activity) result in a microelectrode for H2O2 that exhibits a 2-s response time, a detection limit as low as 2 μM, a sensitivity of 2.75 A cm−2 M−1, and a linear response range from 2 μM to 1.3 mM (R = 0.9994). The sensor is also selective and not interfered by potentially competing species in biological fluids, thus representing an inexpensive but highly sensitive and selective microsensor for H2O2.